Cc2d1a Loss of Function Disrupts Functional and Morphological Development in Forebrain Neurons Leading to Cognitive and Social Deficits. (29th January 2016) - Oaks, Adam W.; Zamarbide, Marta; Tambunan, Dimira E.; Santini, Emanuela; Di Costanzo, Stefania; Pond, Heather L.; Johnson, Mark W.; Lin, Jeff; Gonzalez, Dilenny M.; Boehler, Jessica F.; Wu, Guangying K.; Klann, Eric; et al.
Abstract: Loss-of-function (LOF) mutations in CC2D1A cause a spectrum of neurodevelopmental disorders, including intellectual disability, autism spectrum disorder, and seizures, identifying a critical role for this gene in cognitive and social development. CC2D1A regulates intracellular signaling processes that are critical for neuronal function, but previous attempts to model the human LOF phenotypes have been prevented by perinatal lethality in Cc2d1a -deficient mice. To overcome this challenge, we generated a floxed Cc2d1a allele for conditional removal of Cc2d1a in the brain using Cre recombinase. While removal of Cc2d1a in neuronal progenitors using Cre expressed from the Nestin promoter still causes death at birth, conditional postnatal removal of Cc2d1a in the forebrain via calcium/calmodulin-dependent protein kinase II-alpha ( CamKIIa ) promoter-driven Cre generates animals that are viable and fertile with grossly normal anatomy. Analysis of neuronal morphology identified abnormal cortical dendrite organization and a reduction in dendritic spine density. These animals display deficits in neuronal plasticity and in spatial learning and memory that are accompanied by reduced sociability, hyperactivity, anxiety, and excessive grooming. Cc2d1a conditional knockout mice therefore recapitulate features of both cognitive and social impairment caused by human CC2D1A mutation, and represent a model that could provide much needed insights into the developmental mechanisms underlying nonsyndromic neurodevelopmental disorders.